Modified Crossed Immunoelectrophoresis to Study with Whole Plasma the Reversible Complex Formation of Histidine-Rich Glycoprotein with Plasminogen - Kluft, C; Los, P (Thrombosis and Haemostasis, 1988)
To study the reversible complex formation between the plasma protein histidine-rich glycoprotein (HRG) and plasminogen, crossed immunoelectrophoresis of HRG was modified. In the modification, purified plasminogen was introduced into the gel of the first dimension electrophoresis.Two molecular forms of plasminogen, Glu- and Lys-plasmino-gen, induced a dose-dependent reduction of the electrophoretic mobility of HRG, with a half maximal retardation for both plasminogens at 0.50–0.55 μM of added plasminogen to the agarose gel. HRG in plasma behaved as a uniform fraction with respect to plasminogen binding. In contrast, with the same modified technique another plasma protein, β2-antiplasmin, separated into a retarded plasminogen-binding form and a nonretarded non-plasminogen-binding form.The method can be used to assess several aspects of reversible complex formation between plasma proteins, as demonstrated for plasminogen binding of HRG and α2-antiplasmin in whole plasma.
Keywords: Plasminogen; Histidine-rich glycoprotein; Crossed immunoelectrophoresis; Binding assay; Pα2-antiplasmin; Fibrinolysis